Endogenous Programs and Flexibility in Bird Migration - Åkesson, Susanne; Helm, Barbara (Frontiers in Ecology and Evolution, 2020)
Endogenous programs that regulate annual cycles have been shown for many taxa, including protists, arthropods, fish, mammals and birds. In migration biology, these programs are best known in songbirds. The majority of songbirds rely on a genetic program inherited from their parents that will guide them during their first solo-migration. The phenotypic components of the program are crucial for their individual fitness and survival, and include time components, direction, and distance. This program is constructed to both guide behavior and to regulate flexible responses to the environment at different stages of the annual cycle. The migration program is driven by a circannual rhythm, allowing for, and resetting, carry-over effects. With experience, the migration decisions of individual migrants may be based on information learnt on breeding sites, wintering sites, and en route. At the population level, substantial variation in route choice and timing of migration may be explained by inherited variation of program components, by interactions with environmental and social factors, and by individual learning. In this review we will explore the components of endogenous migration programs and discuss in what ways they can lead to flexibility and variation in migration behavior.